The KMDB/MutationView: a mutation database for human disease genes - Minoshima, Shinsei (Oxford University Press, 2001)
The KMDB/MutationView is a graphical database of mutations in human disease-causing genes and its current version consists of nine category-based sub-databases including diseases of eye, heart, ear, brain, cancer, syndrome, autoimmunity, muscle and blood. The KMDB/MutationView stores mutation data of 97 genes involved in 87 different disease and is accessible through http://mutview.dmb.med.keio.ac.jp.